Size-Dependent Chemistry: Properties of Nanocrystals - Rao, C. N. R.; Kulkarni, G. U.; Thomas, P. John; Edwards, Peter P. (Chemistry : a European journal, 2002)
Properties of materials determined by their size are indeed fascinating and form the basis of the emerging area of nanoscience. In this article, we examine the size dependent electronic structure and properties of nanocrystals of semiconductors and metals to illustrate this aspect. We then discuss the chemical reactivity of metal nanocrystals which is strongly dependent on the size not only because of the large surface area but also a result of the significantly different electronic structure of the small nanocrystals. Nanoscale catalysis of gold exemplifies this feature. Size also plays a role in the assembly of nanocrystals into crystalline arrays. While we owe the beginnings of size‐dependent chemistry to the early studies of colloids, recent findings have added a new dimension to the subject. Fascinating properties are observed for nanoparticles of metals and semiconductors in the quantum size regime. However, these properties often defy conventional notion, since the physical dimension itself emerges as an important parameter determining the electronic, magnetic and the optical properties as well as reactivity and the ability to self‐assemble. The size‐dependent reactivity of gold particles is shown as an example.